Microstrip bandpass filters using triple-mode patch-loaded cross resonator - Zhang, Runqi (2013)
Microstrip bandpass filters using a triple-mode patch-loaded cross resonator are presented in this work. First, a square patch is added at the center of a cross resonator to separate the resonant frequencies of the 1st and 2nd modes. Then, a pair of narrow slots is etched into the square patch along its symmetrical plane to split the 1st resonant mode and its degenerate mode. By changing the patch size and the slot length, the above three modes are appropriately adjusted. Two prototype filters with open-ended and stub-loaded coupled-lines are designed and fabricated to verify the design principle and to further suppress the lowest harmonic passband, respectively. Predicted results agree well with the measured ones.